2022
DOI: 10.3390/cells11162513
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N-Glycoproteins of Knee Cartilage from Adult Osteoarthritis and Kashin-Beck Disease Based on Quantitative Glycoproteomics, Compared with Normal Control Cartilage

Abstract: Glycoproteins are involved in the development of many diseases, while the type and content of N-glycoproteins in the cartilage of osteoarthritis (OA) and Kashin–Beck disease (KBD) are still unclear. This research aims to identify N-glycoproteins in knee cartilage patients with OA and KBD compared with normal control (N) adults. The cartilage samples were collected from gender- and age-matched OA (n = 9), KBD (n = 9) patients, and N (n = 9) adults. Glycoproteomics and label-free liquid chromatography-tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…To further determine the role of TSP-2, exogenous TSP-2 was added to chondroprogenitor cells in microculture and revealed that TSP-2 induced chondrogenic effects on cells. [16,43] A study by Taylor et Table 2 TSP-2-related molecular regulation in chondrogenesis.…”
Section: The Role Of Tsp-2 In Cartilage Regeneration Andmentioning
confidence: 99%
See 2 more Smart Citations
“…To further determine the role of TSP-2, exogenous TSP-2 was added to chondroprogenitor cells in microculture and revealed that TSP-2 induced chondrogenic effects on cells. [16,43] A study by Taylor et Table 2 TSP-2-related molecular regulation in chondrogenesis.…”
Section: The Role Of Tsp-2 In Cartilage Regeneration Andmentioning
confidence: 99%
“…Hankenson KD, et al [41] (2000) The role of TSP-2 in cartilage regeneration and repair hUCB-MSCs/ Cartilage TSP-2 expression is elevated in OA Jeong SY, et al [16] (2013) Han J, et al [43] (2022) Cartilage and bone TSP-2 affects the ratio of bone to cartilage formation…”
Section: The Role Of Tsp-2 In Mesenchymal Stem Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…β- d -Glucuronidase (GUS, EC 3.2.1.31) is widely found in mammalian tissues, plants, insects, and microbes, and its sequences and structures from different sources are homologous . Therefore, its detection has not only the specificity of identifying site structure but also the universality of applications related to cancer treatment course and gut bacteria monitoring. GUS hydrolyzes glucuronide to generate free glucuronic acid and aglycone, the latter of which can be rationally designed and artificially synthesized according to the requirements of different objects to be tested …”
mentioning
confidence: 99%
“…Thus, alkalis are commonly adopted to adjust the pH for achieving a complete dissociation of the probes; however, this will cause GUS deactivation, in tandem with a stoppage of the enzymatic reaction, thereby limiting the applications of these probe molecules such as for some continuous monitoring. (2) The probes are usually applied in an aqueous medium, which may cause the probes to tend to diffuse away from the detection site, thus missing the opportunity to detect GUS in situ. Besides, the relatively short Stokes shift and excitation wavelength suffer from interference from excitation leakage during the detection and imaging of GUS.…”
mentioning
confidence: 99%